Longterm outcomes of auxiliary partial orthotopic liver transplantation in preadolescent children with fulminant hepatic failure. Issue 4 (April 2016) - Weiner, Joshua; Griesemer, Adam; Island, Eddie; Lobritto, Steven; Martinez, Mercedes; Selvaggi, Gennaro; Lefkowitch, Jay; Velasco, Monica; Tryphonopoulos, Panagiotis; Emond, Jean; Tzakis, Andreas; Kato, Tomoaki
Abstract : By preserving part of the native liver, auxiliary partial orthotopic liver transplantation (APOLT) provides the advantage of potential immunosuppression (ISP) withdrawal if the native liver recovers but has had limited acceptance, especially in the United States, due to technical complications and low rates of native liver regeneration. No previous study has evaluated APOLT specifically for preadolescent children with fulminant hepatic failure (FHF). This population might benefit especially based on greater capacity for liver regeneration. Data from 13 preadolescent children who underwent APOLT were compared to 13 matched controls who underwent orthotopic liver transplantation (OLT) for FHF from 1996 to 2013. There were no significant differences in patient demographics or survival between the 2 groups. However, all surviving OLT recipients (10/13) remain on ISP, while all but 1 surviving APOLT recipient (12/13) showed native liver regeneration, and the first 10 recipients (76.9%) are currently off ISP with 2 additional patients currently weaning. In our experience, APOLT produced excellent survival and high rates of native liver regeneration in preadolescent children with FHF. This represents the largest series to date to report such outcomes. Liberating these children from lifelong ISP without the downside of increased surgical morbidity makes APOLT an attractive alternative. In conclusion, we therefore propose that, with the availability of technical expertise and with the technical modifications above, APOLT for FHF should be strongly considered for preteenage children with FHF. Liver Transplantation 22 485‐494 2016 AASLD